2020
DOI: 10.14714/cp96.1631
|View full text |Cite
|
Sign up to set email alerts
|

User-centered Design and Evaluation of a Geovisualization Application Leveraging Aggregated QS Data

Abstract: Individual movement traces recorded by users of activity tracking applications such as Strava provide opportunities that extend beyond delivering personal value or insight to the individual who engages in these “quantified-self” (QS) activities. The large volumes of data generated by these individuals, when aggregated and anonymized, can be used by city planners, Departments of Transportation, advocacy groups, and researchers to help make cities safer and more efficient. This opportunity, however, is constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Tasks used in the reported study included data retrieval or number estimation. Thus, the very low overall correctness rate obtained in the study (20%) confirmed the observations of Netek et al [4] and Nelson and MacEachren [38] about heat maps not being suitable for reading accurate values from maps. Yet, while locating the "hot spots" in T1 compare, or T3 sort, participants did not obtain better results, although heat maps are recommended for such visual analyses [4].…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Tasks used in the reported study included data retrieval or number estimation. Thus, the very low overall correctness rate obtained in the study (20%) confirmed the observations of Netek et al [4] and Nelson and MacEachren [38] about heat maps not being suitable for reading accurate values from maps. Yet, while locating the "hot spots" in T1 compare, or T3 sort, participants did not obtain better results, although heat maps are recommended for such visual analyses [4].…”
supporting
confidence: 84%
“…Thus, we cannot accept Hypothesis 3, stating that heat map users perceive less generalized maps as easier. Perhaps participants from the reported study recognized less generalized heat maps as "visually noisy", similar to those who took part in the study by Nelson and MacEachren [38]. It might also be possible that the results would have been different had the study material been interactive, as in the studies by Roth et al [41,42] and Nelson and MacEachren [38].…”
mentioning
confidence: 74%
See 1 more Smart Citation